Variational principles versus their teleological interpretation - Domaciuk, Dominika (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2008)
In this paper the problem of philosophical interpretation of variational principles is under investigation. The difference between differential and integral principles is presented and the history of various formulations of integral principles is described. It is argued that the teleological interpretation of integral principles is unjustified. Philosophical interpretations of principles of mechanics might only be valuable only if a thorough analysis of both mathematical and linguistic explanations is made.